Evidence of sexual transfer of mycobacteria from male to female partners reporting to an IVF clinic. (April 2022) - Datta, Abira; Gupta, Prabuddha; Bhattacharya, Basudev; Das, Arabinda; Chatterjee, Siddhartha; Banerjee, Asesh
Female genital tuberculosis (GTB) contributes significantly to infertility in low- and middle-income countries. Dissemination of infection from pulmonary and extrapulmonary sites is the major reason for causation of GTB. Additionally, sexual transmission of GTB from male partners has been reported. We selected 81 couples desiring babies from an in vitro fertilization clinic. We used multiplex-PCR for mycobacterial detection in semen of males, in the endometrium of their female counterparts and in the products of conception (POC) from miscarriage. Data interpretation shows that these pregnancies failed owing to sexual transmission of mycobacteria. We noticed by multiplex PCR that mycobacterial infestation in the female can take place in either endometrium or POC from asymptomatic males harbouring mycobacteria in their semen. Therefore, we propose sexual transfer of mycobacteria to be a probable cause of miscarriage. Thus, we suggest multiplex PCR based screening of semen for all males of the couples attempting successful childbirth.